Enhanced transitional heat flux by wicking during transition boiling on microporous hydrophilic and superhydrophilic surfaces. (October 2019) - Li, Jia-Qi; Zhang, Jia-Yi; Mou, Lin-Wei; Zhang, Yu-Hong; Fan, Li-Wu
Highlights: Quenching on microporous hydrophilic and superhydrophilic surfaces was studied. The emphasis was put on the effect of surface wicking on transition boiling regime. The transitional heat flux (THF) was found to increase with improved wickability. The Weber ( We ) number was modified to characterize the surface imbibition of water. A correlation was proposed between the THF enhancement and the modified We number. Abstract: Surface wetting and wicking behaviors have significant effects on the collapse of vapor film, and hence boiling heat transfer, during quenching. In this paper, both hemi-wicking (hydrophilic) and wicking (superhydrophilic) surfaces were fabricated using nanoparticle deposition and chemical etching methods, respectively, on stainless steel spheres. Quenching experiments were carried out on these microporous surfaces in saturated water to reveal the influence of surface wickability on the collapse of vapor film during transition boiling. It was shown that the transitional heat flux (THF) at the critical transitional point, which separates the transitional film boiling sub-regime and transitional nucleate boiling sub-regime, is significantly enhanced with improving the surface wickability, and that the most wickable surface leads to a maximum of 656% THF increase as compared to the bare non-porous surface. The Weber number was modified to characterize the instantaneous imbibition of water through the microporous structures upon liquid-solid contact. Based on the hydrodynamic instability model, a linear correlation was proposed between the enhancement ratio of THF and the modified Weber number.